Prevalencia de comorbilidades en mujeres embarazadas del Hospital de Macará en el año 2020 - Armijos Ramón, María Fernanda (2025)
Pregnancy is the period from conception to childbirth during which certain diseases, known as comorbidities, may occur. The concept of comorbidity can be defined as the coexistence of two or more diseases in an individual, which may arise during pregnancy due to poor medical monitoring and follow-up, inadequate supplement intake, poor nutrition, lack of exercise, or excessive physical activity, all of which can lead to a high-risk pregnancy. The general objective of this study was to analyze the prevalence of comorbidities in pregnant women at Macará Hospital in 2020. The specific objectives included characterizing the sociodemographic profile of the pregnant women receiving medical care, determining the prevalence of comorbidities during pregnancy, and promoting preventive actions against comorbidities in pregnancy. Regarding the methodology, this study follows a quantitative approach, utilizing data from PRAS (Health Care Registration Platform) and perinatal medical records from Macará Hospital in 2020. The results indicated a significant prevalence of comorbidities among pregnant women aged 15 to 20, of Ecuadorian nationality, residing in urban areas, with a high school education level, and predominantly single. According to the ICD-10 (International Classification of Diseases, 10th edition), the most common comorbidities were other and unspecified infections of the genitourinary tract during pregnancy, with a prevalence of p = 0.15, followed by genital infections during pregnancy (p = 0.13) and low weight gain during pregnancy (p = 0.10). In conclusion, this study highlights that the most prevalent comorbidities are genital and urinary infections, affecting 49% of cases, followed by different types of anemia, which account for 19%